2022
DOI: 10.1186/s43162-021-00094-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinico-bacteriological profile and antibiotic resistance pattern in patients with acute exacerbation of COPD

Abstract: Background Repeated attacks of acute exacerbations of chronic obstructive pulmonary disease (AECOPD) have been attributed to bacterial infections. However, sputum microbiology for identifying the bacteriological profile is not performed usually and remains controversial. Thus, we performed a prospective, cross-sectional study to assess the clinico-bacteriological profile of the patients with AECOPD and antibiotic resistance pattern of bacteria isolated from sputum samples. The study involved 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…However, these findings differ significantly from those in Hong Kong [ 33 ] and Western countries such as the UK [ 32 ], where community-acquired pneumonia (CAP) ( H. influenzae, S. pneumoniae, and M. catarrhalis ) was associated with AE-COPD. Interestingly, these outcomes are contrary to those of Mood et al in India [ 35 ] and Mussema et al in Ethiopia [ 36 ]. These authors found that the most common bacterial isolate was P. aeruginosa , followed by K. pneumoniae and either S. pneumoniae or S. aureus .…”
Section: Discussioncontrasting
confidence: 85%
“…However, these findings differ significantly from those in Hong Kong [ 33 ] and Western countries such as the UK [ 32 ], where community-acquired pneumonia (CAP) ( H. influenzae, S. pneumoniae, and M. catarrhalis ) was associated with AE-COPD. Interestingly, these outcomes are contrary to those of Mood et al in India [ 35 ] and Mussema et al in Ethiopia [ 36 ]. These authors found that the most common bacterial isolate was P. aeruginosa , followed by K. pneumoniae and either S. pneumoniae or S. aureus .…”
Section: Discussioncontrasting
confidence: 85%
“…However, these ndings differ signi cantly from those in Hong Kong [27] and Western countries such as the UK [26], where community-acquired pneumonia (CAP) (H. in uenzae, S. pneumoniae, and M. catarrhalis) was associated with AE-COPD. Interestingly, these outcomes are contrary to those of Mood et al in India [29] and Mussema et al in Ethiopia [30]. The authors found that the most common bacterial isolate was P. aeruginosa, followed by K. pneumoniae and either S. pneumoniae or S. aureus.…”
Section: Discussionmentioning
confidence: 67%
“…In a recent study conducted at the All India Institute of Medical Sciences (AIIMS), Bhubaneswar, the mean age was 65.49 ± 10.40 years [ 7 ]. As per another Indian study by Mood et al, the mean age of patients was 66.8 ± 11.4 years and the maximum prevalence was observed in the age group 70-79 years [ 8 ]. In another study that involved both European and American subjects, the proportion of females was 36.7% among Europeans and 33.3% among Americans, which is in accordance with our findings [ 9 ].…”
Section: Discussionmentioning
confidence: 82%
“…A study by Hajare et al reported a male-to-female ratio of 2.3:1 [ 10 ]. The preponderance of males being affected can be attributed to the fact that males are more involved in outdoor activities and hence are more exposed to environmental pollutants [ 8 ]. Smoking is a risk factor for COPD and also its exacerbation as it decreases mucociliary clearance, which is amply proved in our study where smoking as a risk factor was noticed among 64% of patients [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation